2020
DOI: 10.32479/ijeep.10345
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renewable Energy on Sustainable Economic Growth in Vietnam

Abstract: This research is aimed to evaluate the impact of renewable energy on sustainable economic growth (SEG) by developing the role of mediating variable such as sustaining energy supply (SES). We use qualitative and quantitative technique such as Covariance -Based Structural Equation Model (CB-SEM) to analyze the data of collection from experts, economists, executives in Vietnam in 2020. The study has proved the five components of renewable energy such as solar energy (SEN), hydro energy (HEN), wind energy (WEN), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Anwar et al (2021) examined the impact of public private investment partnership in transportation, REC, urbanisation, and economic growth on transportation-induced carbon emissions over the period of 1990Q1–2018Q4 by applying Quantile Autoregressive Distributed Lag (QARDL) methodology. Tiep, Huan, and Hong (2020) examined impact of renewable energy on sustainable economic growth for Vietnam by employing covariance based structural equation model (CB-SEM). The study suggested positive impact of solar, hydro, wind, bio and geothermal energy on sustainable energy supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anwar et al (2021) examined the impact of public private investment partnership in transportation, REC, urbanisation, and economic growth on transportation-induced carbon emissions over the period of 1990Q1–2018Q4 by applying Quantile Autoregressive Distributed Lag (QARDL) methodology. Tiep, Huan, and Hong (2020) examined impact of renewable energy on sustainable economic growth for Vietnam by employing covariance based structural equation model (CB-SEM). The study suggested positive impact of solar, hydro, wind, bio and geothermal energy on sustainable energy supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It create domestic and regional economic opportunities, enhance the scope of domestic production, and augment exports of local products. Environmentally friendly energies are those renewable resources that do not adversely affect the quality of the environment, are infinite, are relatively cheaper over protracted periods, and are sustainable in the future (Huan & Hong, 2020). Green energy is the sole factor of production and is the solution to future environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to environmental sustainability, renewable energy is viewed as a way for a country to achieve many objectives, such as improving energy access, reducing air pollution, and improving the environment. These objectives benefit not only the economy but also the environment and the living standards of a nation's people (Huan and Hong, 2020). Renewable and alternative energy (clean energy) sources like wind, solar, biofuels, hydro, and others are the foundation for the energy transition to a low or zero dioxide and sustainable energy system (Khan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%